Perlindungan Hukum terhadap Pemegang Hak atas Tanah dalam Sengketa Kepemilikan Berdasarkan Alat Bukti Girik: Studi Putusan Mahkamah Agung Nomor 1559 K/Pdt/2025 - Rina Revitha Sari Nasution; Rosnidar Sembiring; maria (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Girik is not proof of land ownership rights but merely evidence of customary land control and tax payment; therefore, it cannot be equated with a land certificate. This study examines the legal status of girik as evidence, the legal protection of its holders against holders of Freehold Title Certificates and the legal reasoning of the Supreme Court in Decision Number 1559 K/Pdt/2025. The research employs a normative legal method with statutory and case approaches. The results indicate that girik serves only as preliminary evidence, while legal protection is both preventive and repressive. The Supreme Court emphasizes that girik lacking a clear administrative basis cannot outweigh the evidentiary strength of a land certificate and highlights the importance of orderly land administration in legal proof.